Self-determination as a will? Hegel’s doctrine of free spirit and the fundamental axiotic relationship of transcendental philosophy to Kantianism - Krijnen, Christian; Kubalica, Tomasz (Folia Philosophica, 2011)
The problem of social ontology in relation to the philosophy of German idealism requires a systematic settlement on the ground of this tradition, which would be also directed against the background of ‘transcendental philosophies of Kantianism’. Their doctrine of the fundamental axiotic relationship is understood as a ‘primacy of practical reason’ and ‘unity of theoretical and practical reason’. This essay analyzes how the fundamental axiotic relationship is understood in Hegel’s philosophy. On the one hand Hegel was aware of the need of overcoming the traditional opposition between theoretical and practical reason, but on the other side he included it in his work.